Pengaruh Perputaran Piutang dan Perputaran Persediaan Terhadap Return on Asset Pada PT. Catur Sentosa Adiprana, Tbk - Wahyudi Putra, Rizky; Rahman, Agussalim; Umar (Khazanah Journal: Economics, Muamalah & Entrepreneurship, 2024)
The purpose of this study was to determine the effect of accounts receivable turnover and inventory turnover on return on assets simultaneously and partially. The research method used is multiple linear regression analysis method, correlation coefficient (R), coefficient of determination (R2), f test (simultaneous) and t test (partial). The results of the multiple linear regression equation research are Y = -9.440 + 0.728X1 + 6.099X2, correlation coefficient test of 0.8046, coefficient of determination of 64.73%, f count value < f tabel (2.75 < 9.55) and t count value < t table b1 (2.274 < 2.353), t count value < t table b2 (0.955 < 2.353). This shows that accounts receivable turnover and inventory turnover simultaneously have an insignificant effect on return on assets, while partially the variable accounts receivable turnover and inventory turnover have a positive but insignificant effect on the return on assets variable.